2017
DOI: 10.1163/15685411-00003114
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short-term growth of mung bean and its soil incorporation on the density of the soybean cyst nematode, Heterodera glycines, in pot experiments

Abstract: We previously reported that incorporation of bean sprout residue into soil stimulated hatching of the soybean cyst nematode (SCN), Heterodera glycines. The objective of this study was to evaluate the effects of short-term growth of mung bean (Vigna radiata), the raw material of bean sprout, and its incorporation into the soil on the density of SCN in soil. When mung bean was grown in pots for 2 and 4 weeks in a SCN-infested andosol, incorporated into the soil and further incubated for 2 weeks, the SCN density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…We previously reported that short-term growth and incorporation of mung bean in pots stimulated SCN hatching and then decreased SCN density (Chikamatsu et al, 2017).…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…We previously reported that short-term growth and incorporation of mung bean in pots stimulated SCN hatching and then decreased SCN density (Chikamatsu et al, 2017).…”
Section: Discussionmentioning
confidence: 95%
“…This study was conducted to show whether short-term cultivation of mung bean and its ploughing in fields decreased the population density of SCN in the soil. Two climatic factors are mainly involved in the efficacy to decrease SCN density: temperature and moisture (Chikamatsu et al, 2017). In previous studies, different optimal temperatures were reported for SCN hatching.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations